Genetic overlap between multi-site chronic pain and cognition: a large-scale genome-wide cross-trait analysis - Chen, Yanjing; Deng, Jiankai; Zhang, Zhiyi; Wang, Chenlin; Yu, Xuegao (Frontiers in Neuroscience, 2025)
BackgroundDifferent studies have consistently demonstrated a positive correlation between chronic pain and cognitive changes. This study aimed to explore the genetic factors underlying the relationship between chronic pain and cognitive traits, and to investigate whether an inherent causal connection exists between them.MethodThe genetic contributions of chronic multi-site pain and eight cognitive traits were investigated based on Genome-wide association studies (GWAS) data. Linkage disequilibrium score regression (LDSC) was employed to assess the genetic correlations between each pair of traits. The shared genetic components of these traits were investigated by identifying single nucleotide polymorphisms (SNPs) with pleiotropic effects using the Cross Phenotype Association (CPASSOC) method. Furthermore, enrichment analysis and transcriptome-wide association studies (TWAS) were performed to characterize the significant associations between genetic traits. The latent causal variable model (LCV) was employed to explore the potential causal relationship between both traits.ResultsA significant negative genetic correlation was found between chronic pain and several cognitive functions, particularly intelligence (rg = −0. 11, p = 7.77 × 10−64). CPASSOC identified 150 pleiotropic loci. A co-localization analysis was conducted, which identified 20 loci exhibiting pleiotropic effects at the same genomic position. The LCV analysis indicated no causal relationship between both traits.ConclusionThe present work contributed to an enhanced understanding of the complex genetic interplay between cognitive function and chronic pain.